2014
DOI: 10.1038/mt.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

The Strength of the T Cell Response Against a Surrogate Tumor Antigen Induced by Oncolytic VSV Therapy Does Not Correlate With Tumor Control

Abstract: Cancer therapy using oncolytic viruses has gained interest in the last decade. Vesicular stomatitis virus is an attractive candidate for this alternative treatment approach. The importance of the immune response against tumor antigens in virotherapy efficacy is now well recognized, however, its relative contribution versus the intrinsic oncolytic capacity of viruses has been difficult to evaluate. To start addressing this question, we compared glycoprotein and matrix mutants of vesicular stomatitis virus (VSV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Stimulation of innate immune mechanisms and the induction of anti-tumoral CTLs are more crucial factors for tumor control [ 30 ]. Janelle et al showed that VSV replicates in subcutaneous B16 tumors for only a few days after intratumoral injection [ 31 ]. We made similar observations for VSV-GP using a virus variant expressing luciferase.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of innate immune mechanisms and the induction of anti-tumoral CTLs are more crucial factors for tumor control [ 30 ]. Janelle et al showed that VSV replicates in subcutaneous B16 tumors for only a few days after intratumoral injection [ 31 ]. We made similar observations for VSV-GP using a virus variant expressing luciferase.…”
Section: Discussionmentioning
confidence: 99%
“…Even though VSV has immunostimulatory abilities by itself, many approaches are being investigated to rationally improve tumour-specific immunity [114]. Most of the studies are aimed at improving tumour-specific T-cell responses, however it is important to mention that studies have shown that the capacity to induce a stronger immune response against a tumour antigen does not always correlate with improved therapeutic efficacy [115].…”
Section: Inducing Tumour-specific Immunitymentioning
confidence: 99%
“…1 There is now considerable evidence that the ability of oncolytic virotherapy to control local disease involves both direct viral oncolysis and multiple host-derived effectors of the innate and adaptive immune system. 2,3 Moreover, we, and others, have focused on understanding how systemically delivered viral therapies may be used to mount a systemic anti-tumor response against widely disseminated metastatic disease, a major challenge to effective cancer therapy.…”
Section: Introductionmentioning
confidence: 99%